Topics in urban economics: Non-market valuation and location choice - Maria Hansen (University of Copenhagen, Department of Economics, 2019)
This dissertation consists of three self-contained chapters on topics in urban economics. They complement each other by taking three different angles on what drives the decisions on where to live, and in chapter 2 and 3 also where to work.
Keywords: 330